SIMULASI PERHITUNGAN ACTIVITY BASED COSTING SEBAGAI ALTERNATIF PENENTUAN HARGA POKOK PRODUK - Cokorda Gde Bayu Putra (UNHI Press, 2020)
Competition in the manufacturing industry encourages various companies to think about strategies for determining the cost of production that is appropriate and accurate. The accurate calculation of the cost of production has an impact on determining an increasingly competitive selling price. This article tries to describe how companies engaged in convection to calculate the cost of production based on Activity Based Costing. The method used in this article is a qualitative method by calculating case studies on quantitative paradigm and comparing the calculation of conventional production costs with Activity Based Costing calculations. This study was conducted at PT. Tirtha Bulan Bali, a garment that carries out production based on the order method.Through this article, it is produced that Activity Based Costing produces cost of production more accurate because overhead costs are charged to products using more cost drivers both unit and non-unit based.